Effect of Follicular Fluid on Attainment of Puberty in Female Halfbred (Beetal X Black Bengal) Kids - SHAH, K A; SHRIVASTAVA, A K; SINHA, A K; SINGH, D K; SINGH, R A (The Indian Journal of Animal Reproduction, 2023)
24 female halfbred (BT x BB) kids of about 12 weeks of age were used for induction of  puberty by administration of follicular fluid (FF).The study was conducted in three groups, A (3ml FF), B ( 1ml FF) and C (untreated control).Kids were exposed to teaser buck daily both morning and evening throughout the period of experiment for detection of first estrus which wastaken as indicator for attainment of puberty. Kidstreated with 1 ml ( 165.50±3.50 days) and 3ml ( 160.66±2.72 days) follicular fluid attained pubety significantly earlier than those of untreatedcontrol (201.50±0.50).
Keywords: Follicular Fluid; Female Halfbred